ZONA KERENTANAN AIRTANAH TERHADAP KONTAMINAN DENGAN METODE DRASTIC - Putranto T.T Putranto T.T; Benny Kuswoyo (TEKNIK, 2008)
Almost all groundwater resources are vulnerable to various degrees. Vulnerability of groundwater is arelative, dimensionless property that is not directly measurable. It is assesed by using the DRASTICtechnique. The accuracy of its assessment depends, above all, on the amoun and quality of representativeand reliable data available. The required data is often not available and thus scale of mapping os oftenlimited to broad scale catchment maps. The DRASTIC vulnerability mapping technique can generally bereferred to as a composite description of all the major geologic and hydrogeologic factors that affect andcontrol groundwater movement, into, through and out of an area. DRASTIC is an acronym for the mostimportant mappable features within the hydrogeologic setting which control groundwater pollution.These features are: D (Depth to watertable), R (Net) Recharge, A (Aquifer media), S (Soil media), T(Topograhy/slope), I (Impact of vadoze zone) and C (hydraulic Conductivity of aquifer).